Effectiveness of Compassion-Focused Therapy on Occupational Stress and Distress Tolerance in Emergency Department Nurses - Shaghaghi, Sara; Jahani, Jalal; Ghorbanpour Ahmadsargourabi, Farzaneh; Mostafavi, Elham (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the effectiveness of Compassion-Focused Therapy on occupational stress and distress tolerance among emergency department nurses. The research employed a quasi-experimental pretest-posttest design with a control group. The statistical population comprised all emergency department nurses working in Rasht county hospitals in 2025. Using convenience sampling, 40 nurses were selected and randomly assigned (via lottery) to the experimental group (20 participants) and the control group (20 participants). Data collection instruments included the Emotional Distress Tolerance Questionnaire by Simmons and Gaher (2005) and the Occupational Stress Questionnaire by Krishna and Srivastava (1991). The experimental group received 8 weekly sessions, twice a week (2 hours each) of Compassion-Focused Therapy by Gilbert (2009). Data were analyzed using multivariate analysis of covariance (MANOVA) via SPSS-27. Results indicated a significant reduction in occupational stress and a significant increase in distress tolerance in the experimental group compared to the control group. Compassion-Focused Therapy was effective in reducing occupational stress and enhancing distress tolerance among emergency department nurses.